Emergy-based evaluation of world coastal ecosystem services. (1st October 2021) - Liu, Chang; Liu, Gengyuan; Yang, Qing; Luo, Tianyi; He, Ping; Franzese, Pier Paolo; Lombardi, Ginevra Virginia
Highlights: An emergy-based marine ecosystem service classification and accounting method has been established. Emergy can quantify the cumulative available energy expenditure to evaluate environmental cost from contributor perspective. Asia and North America contribute about 55% of the global coastal ecosystem service value. Estuaries have the highest ecosystem service values, followed by mangroves, seagrass beds, tidal flats, salt marshes. Developed countries still occupy an advantageous position in the process of marine protection, development and utilization. Abstract: The current lack of research on the evaluation of marine ecosystem services makes the value of marine protection, development and restoration underestimated during the decision-making process. Based on the non-monetary ecosystem service evaluation framework, a marine ecosystem service classification and accounting method has been established in this study, and the world's coastal ecosystem services have been measured as an example. The results show that (1) the world's coastal ecosystem service value is about 4.13E+23 sej/yr, of which Asia and North America contribute about 55% of the total service value; (2) the top ten countries in terms of the world's coastal ecosystem service values are Canada, Indonesia, Australia, the United States, Brazil, the Russian Federation, Norway, the Philippines, Mexico, and China, which contribute about 60% of the total service value; (3) estuaries have the highest ecosystem service values, followed by mangroves, seagrass beds, tidal flats, salt marshes, and warm water coral reefs; (4) developed countries can make better use of their coastal resources and pay more attention to the marine protection while the opposite is true in developing countries, which means that developed countries still occupy an advantageous position in the process of marine protection, development and utilization. This study assesses the coastal ecosystem service values in various coastal countries from the perspective of ecosystem contributors, emphasizes the importance of protecting them in marine management, and provides a certain reference basis and theoretical support for decision-makers in formulating marine-related protection and development strategies. Graphical abstract: Image, graphical abstract